Regeneration potentials of native tree species in three natural forests of Sylhet, Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Natural regeneration status of native tree species in three natural forests of Moulvibazar, Sylhet Forest Division, Bangladesh was assessed through stratified random sampling method. A total of 70 tree species belonging to 31 families was recorded. Moraceae has the maximum number of species (8 species). Myrtaceae has 6 species and Rubiaceae has 5 species while both Euphorbiaceae and Meliaceae have 4 species each. The families Anacardiaceae, Bignoniaceae, Combretaceae, Fagaceae, Lauraceae, Sterculiaceae, Verbenaceae have 3 species each, while Clausiaceae, Mimosaceae and Ternstroemiaceae has 2 species each, and the rest 16 families (viz. Apocynaceae, Aquifoliaceae, Araliaceae, Arecaceae, Bombacaceae, Burseraceae, Caesalpinaceae, Dilleniaceae, Dipterocarpaceae, Elaeocarpaceae, Lythraceae, Myrsinaceae, Polygalaceae, Rutaceae, Tiliaceae, Thymelaeaceae) comprise one species each. Artocarpus chama represents maximum seedlings production per hectare (2,528), followed by Syzygium firmum (1825), Ficus racemosa (1425), Syzygium fruticosum (1033) and Holigarna caustica (917). Biological diversity indices were also calculated which ensure a promising regeneration status of Moulvibazar Natural forests. The percentage distribution of seedlings was maximum (78.12%) for 0-50 cm height range for all species. The numbers of seedling reduced proportionately with height growth indicating the reduction recruitment of seedlings in Moulvibazar natural forests. Artocarpas chama showed maximum (1.97 %) seedling recruitment. Natural regeneration potential is useful for developing the management plans for effective functioning of Moulvibazar natural forests, Sylhet, Bangladesh.J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(2): 1-10